2002
DOI: 10.1097/00004424-200202000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Potential of Targeted Electrical Impedance Scanning in Classifying Suspicious Breast Lesions

Abstract: EIS showed mediocre overall diagnostic accuracy for classifying suspicious breast lesions. Quantitative analysis of positive EIS findings did not help to differentiate between false and true positive spots.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
1
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 10 publications
2
21
1
1
Order By: Relevance
“…Moreover, one study claimed that the area under the ROC curve was significantly higher for TS2000 than other imaging methods (6). In contrast to these reports, there are two studies that found mediocre diagnostic effectiveness of impedance imaging (13,19). Our study supports the high rate of false-positive findings of TS2000 continuing to be an issue, and this limitation prevents wide clinical use of the technology.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Moreover, one study claimed that the area under the ROC curve was significantly higher for TS2000 than other imaging methods (6). In contrast to these reports, there are two studies that found mediocre diagnostic effectiveness of impedance imaging (13,19). Our study supports the high rate of false-positive findings of TS2000 continuing to be an issue, and this limitation prevents wide clinical use of the technology.…”
Section: Discussionsupporting
confidence: 77%
“…Several clinical trials have been conducted to test this modality, and these have suggested that TS2000 has adjunctive value to conventional imaging methods, especially in mammographically suspicious lesions (6,(10)(11)(12). However, other studies have not confirmed these findings (13,19).…”
mentioning
confidence: 99%
“…Malich et al have demonstrated the specifi city rates of EIS in sonographically visible and not visible benign lesions as 63 % and 67 %, respectively (25). Wersebe et al have also demonstrated comparable specifi city rates in proliferative and non-proliferative benign breast lesions as 67 % and 71 %, respectively (26). These reports have demonstrated similar, but insuffi cient outcomes to evaluate true negative results in mammographic BIRADS III lesions 13.…”
Section: Discussionmentioning
confidence: 99%
“…EIS has been recently described in many articles as an invaluable and effi cient screening modality for benign and malignant diseases of the breast (21)(22)(23)(24)(25)(26)(27). EIS evaluates the electrical activity of the breast and surrounding tissue so that lower electrical impedance-conductivity rates of the lesion compared to the surrounding tissue represent a malignant disease (28).…”
Section: Discussionmentioning
confidence: 99%
“…TS2000 is a real-time, non-invasive method for measurement of increased conductivity and capacitance in malignant tumours and is done on the skin surface of the breast. Some studies report about varying sensitivity values even when using EIS in similar study designs [6,7,8,9,10]. From theoretical simulations it is known that the technology of electrical impedance scanning is limited in the evaluation of lesions located deeper then 3.5 cm from the skin surface [11].…”
Section: Introductionmentioning
confidence: 99%